Patients' experiences of coping with multiple chronic conditions: A meta‐ethnography of qualitative work. (19th September 2018) - Cheng, Cheng; Inder, Kerry; Chan, Sally Wai‐Chi
Abstract: Multiple chronic conditions (MCCs) pose a major and growing burden on the individuals' health. The ways in which people cope with their stresses related to their chronic conditions are significant to their health outcomes. This review sought to understand lived experiences of coping with MCCs by a meta‐ethnography of qualitative studies. Twenty‐six studies were identified in four electronic databases including PubMed, PsycINFO, EMBASE, and CINAHL that were searched from 1966 to 2017. A seven‐step analytic method was used after a quality evaluation based on Joanna Briggs Institute Qualitative Assessment and Review Instrument (JBI‐QARI). The findings illustrated that experiences of coping with MCCs were interacted with (i) appraisals of MCCs, (ii) strategies to maintain a normal life, (iii) strategies to keep the spirits up, and (iv) coping in the social context. To sum up, this review provided a collection of narratives on coping with MCCs. The findings would help to recognize the high complexity experienced by these patients, also potentially offered a foundation for the design of a feasible intervention to more optimally highlight the demands of managing MCCs.